Electronics, Communications and Networks V Proceedings of the 5th International Conference on Electronics, Communications and Networks (CECNet 2015) - Hussain, Amir (Lecture Notes in Electrical Engineering, 2016)
This book comprises peer-reviewed contributions presented at the 5th International Conference on Electronics, Communications and Networks (CECNet 2015), held in Shanghai, China, 12-15 December, 2015. It includes new multi-disciplinary topics spanning a unique depth and breadth of cutting-edge research areas in Electronic Engineering, Communications and Networks, and Computer Technology. More generally, it is of interest to academics, students and professionals involved in Consumer Electronics Technology, Communication Engineering and Technology, Wireless Communication Systems and Technology, and Computer Engineering and Technology.